Conception of Lifelong Education as a Factor of Life Quality Improving for Third Age People (by the example of Education in Poland) - Z V Boyko; E V Belovol; Maria Groenwald; Wojciech Siegień (Peoples' Friendship University of Russia (RUDN University), 2014)
The problem of the third age people's education is considered in the article. The conception of lifelong education as well as its realization in Western European countries is analyzed. The situation of creating and developing universities for the third age people is examined by the example of Poland.